Soil organic carbon measurements influence FT‐NIR model training in calcareous soils of Saskatchewan - Adejumo, Gbenga; Bulmer, David; Sorenson, Preston; Peak, Derek (Soil Science Society of America journal, 2025)
This study compares acid digestion and temperature ramping methods for obtaining soil organic carbon (SOC) reference data to train Fourier transform near infrared (FT‐NIR) models in carbonate‐rich Saskatchewan agricultural soils. FT‐NIR spectra were measured on soil samples (n = 431) from carbonate‐rich Dark Brown Chernozem soil, with quantification of inorganic and organic carbon. Spectra were transformed using continuous wavelet transform and analyzed using cubist regression tree models. Models were built using a 70:30 train test split validation approach. Spectral feature selection, wavelet scale, and model and hyperparameter optimization were conducted using fivefold cross‐validation analysis on the training dataset. All validation metrics were calculated using the testing dataset. The temperature ramping method identified outliers with soil inorganic carbon (SIC) greater than 1.5%, which were not detected using the acid digestion method. SOC and SIC prediction accuracy was higher using temperature ramping data (coefficient of determination: R2 = 0.66 and 0.63, Lin's concordance: ccc = 0.78 and 0.77) compared to acid digestion data (R2 = 0.44 and 0.42, ccc = 0.64 and 0.62). Total carbon (TC) prediction accuracy was similar for both methods (R2 = 0.58, ccc = 0.71). Removing samples with high carbonate (SIC > 1.5%) improved SOC and TC prediction accuracy using temperature ramping data (R2 = 0.70, ccc = 0.81 for SOC; R2 = 0.64, ccc = 0.75 for TC) but not when using acid digestion method. This study suggests that high carbonate content may negatively affects SOC model accuracy, especially when relying upon acid digestion methods for reference SOC data. Core Ideas Soils with high carbonate contents are challenging for modeling soil organic carbon (SOC) with Fourier transform near infrared reflectance (FT‐NIR) spectra. Reference data for training SOC model affects model performance in carbonate‐rich soil. Temperature ramping generates more reliable SOC reference data.